Application of a check-all-that-apply question for evaluating and characterizing meat products. (February 2015) - Jorge, Élida da Conceição; Mendes, Andressa Cristina Gaione; Auriema, Bruna Emygdio; Cazedey, Henrique Pereira; Fontes, Paulo Rogério; Ramos, Alcinéia de Lemos Souza; Ramos, Eduardo Mendes
Abstract: Four different mortadella samples were technologically characterized by physical/chemical and instrumental analyses and were sensorially characterized by acceptance testing and check-all-that-apply (CATA) questions. Samples were divided into three groups by using a principle component analysis (PCA) of the technological characteristics and by using an internal preference map (IPM) of the sensory attributes from the acceptance test. CATA divided these samples into four different external preference map (EPM) groups because each sample was associated with different sensory attributes. The PCA indicated that there was a relationship between the instrumental color and texture analyses and the CATA attributes, whereby identifying the terms that positively or negatively contributed to sample acceptance. The CATA questions effectively discriminated between the meat products regarding their sensory characteristics. In addition, these attributes were linked to chemical and instrumental quality parameters. Thus, the CATA questions are a potential tool for evaluating and developing novel products. Highlights: We used check-all-that-apply (CATA) as a sensory analysis tool for meat products. Mortadella samples were sensorially characterized by acceptance testing and CATA. PCA and IPM of sensory acceptance test divided samples into three groups. The CATA discriminated the four mortadellas regarding their sensory characteristics.